2021
DOI: 10.3390/su13137185
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Poor Neighborhoods through the Lenses of the Capability Approach—A Case Study of a Deprived Area of Łódź City Centre

Abstract: The aim of the paper is to identify the mechanisms shaping the quality of life of the residents of poor neighborhoods based on the example of a deprived area of Łódź city center. To analyze this multidimensional phenomenon, the capability approach is used with a special focus on conversion factors that limit the pursuit of preferred lifestyles. Based on 80 in–depth interviews with residents and register data from public authorities (at the building level, which enables presenting the detailed spatial distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…So it is necessary to socialize the mechanism of the Waste Bank system, one of which is sorting household waste. This positive perception is formed mainly due to the living environment conducive to implementing household waste management [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So it is necessary to socialize the mechanism of the Waste Bank system, one of which is sorting household waste. This positive perception is formed mainly due to the living environment conducive to implementing household waste management [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…These results align with the principle that the neighborhood is the third important context that shapes the quality of life, besides family and school. The Children's Worlds survey also showed that neighborhood factors can explain variations in children's life satisfaction, even after considering demographic factors and family and school-related factors [12,13,21]. Empowerment in environmental management is one of the principles of ecological development.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the fact that quality of life is a complex concept [45], it is not possible to provide a single accurate definition [46]. Some of the definitions of this concept are more general, such as "the level of what makes life good or high quality" [47] or that it is the "necessary preconditions for happiness" [48]; meanwhile, others are more specific: "a quality way of life is the desired outcome of policies and programs" [49].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, they point out that there is a clear feminization of poverty despite the fact that the city's population of women is approximately 50% [98]. The complexity of negative phenomena in poor neighborhoods overlaps with the already multidimensional phenomenon [99]. The recently developed Urban Land Plan of Castellón identified vulnerable areas in the city and a previous model was used to assess vulnerability [52].…”
Section: Case Studymentioning
confidence: 99%